Beginning Rails 6 : from novice to professional - Somerville, Brady; Gamble, Adam; Carneiro, Cloves; Al Barazi, Rida (Apress, 2020)
Springboard your journey into web application development and discover how much fun building web applications with Ruby on Rails can be. This book has been revised to cover what's new in Rails 6 including features such as WebPack, advanced JavaScript integration, Action Mailbox, Action Text, system and parallel testing, Action Cable testing, and more. Beginning Rails 6 gently guides you through designing your application, writing tests for the application, and then writing the code to make your application work as expected. It is a book that will guide you from never having programmed with Ruby, to having a Rails 6 application built and deployed to the web. After reading and using this book, you'll have the know-how and the freely available source code to get started with your own Rails-based web development in days. You will: Create Ruby on Rails 6 web applications from the bottom up Gain the basics of the Ruby programming language Combine all the components of Rails to develop your own web applications Apply TDD to make sure your application works exactly as you expect Use Git source control and best practice techniques to create applications like a pro.